2019
DOI: 10.1002/jbm4.10080
|View full text |Cite
|
Sign up to set email alerts
|

CSF‐1 in Osteocytes Inhibits Nox4‐mediated Oxidative Stress and Promotes Normal Bone Homeostasis

Abstract: CSF-1 is a key factor in regulating bone remodeling; osteocytes express CSF-1 and its receptor. Viable osteocytes are essential for bone remodeling through cell-cell contact and secretion of factors that regulate osteoblasts and osteoclasts. Increased oxidative stress contributes to osteocyte death and correlates with bone loss during aging. The NADPH oxidase Nox4 is a major source of ROS in bone. CSF-1 decreases Nox4, suggesting that CSF-1 protects against oxidative stress. Here, we show that osteocyte apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 69 publications
1
20
0
Order By: Relevance
“…Many data relate high levels of reactive oxygen species (ROS) to defective bone remodeling and mineralization processes regulated by osteoblast and osteoclast activity [20][21][22][23][24], and controlled by osteocytes, through secretion of factors that can modulate both bone formation and resorption [25][26][27]. It has also been demonstrated that high levels of ROS induce marked apoptosis in osteoblasts and osteocytes [27][28][29][30], and both oxidative stress and osteocyte apoptosis are linked to deficiency of estrogens, the aging process and chronic glucocorticoid treatment with consequent decrease in bone mineral density [15,31,32]. In fact, ovariectomy increases osteocyte apoptosis, leading to the accumulation of bone microdamage unable to be repaired through the bone remodeling process, with consequent abnormal activation of osteoclast activity [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Many data relate high levels of reactive oxygen species (ROS) to defective bone remodeling and mineralization processes regulated by osteoblast and osteoclast activity [20][21][22][23][24], and controlled by osteocytes, through secretion of factors that can modulate both bone formation and resorption [25][26][27]. It has also been demonstrated that high levels of ROS induce marked apoptosis in osteoblasts and osteocytes [27][28][29][30], and both oxidative stress and osteocyte apoptosis are linked to deficiency of estrogens, the aging process and chronic glucocorticoid treatment with consequent decrease in bone mineral density [15,31,32]. In fact, ovariectomy increases osteocyte apoptosis, leading to the accumulation of bone microdamage unable to be repaired through the bone remodeling process, with consequent abnormal activation of osteoclast activity [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…ROS has a negative effect on bone homeostasis due to its pro-osteoclastic effects [ 40 ]. Oxidative stress causes dysfunction of bone metabolism-related cells including bone mesenchymal stem cells [ 41 ], osteoblasts [ 42 ], osteoclasts [ 43 ], and osteocytes [ 44 ]. Glucocorticoids stimulate overproduction of ROS by depletion of antioxidant molecules or inhibition of antioxidant enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Continuous production of M-CSF in osteocytes enhances osteoclastogenesis [ 93 ]. Osteocyte-derived M-CSF protects against excessive Nox4-derived ROS generation and retains bone remodeling [ 94 ].…”
Section: Periodontitis: Osteoimmunologymentioning
confidence: 99%